HAMBATAN PENERAPAN SANKSI PIDANA TERHADAP PELAKU PEMBUANGAN SAMPAH TIDAK PADA TEMPATNYA DI KABUPATEN TIMOR TENGAH SELATAN - Maria E. Y. W. Napa; Jimmy Pello; Bhisa Vitus Wilhelmus (Petitum Law Journal, 2026)
This study explores the challenges in implementing criminal sanctions against individuals who litter in Soe City, South Central Timor Regency, which is based on Regional Regulation Number 4 of 2018 concerning Waste Management. The method applied in this study is empirical law with the use of a qualitative approach, involving structured interviews with government officials, police, and the community, as well as field observations and document analysis. The results of this study found six factors that hinder implementation: (1) weak law enforcement by the Department of Environment, Civil Service Police Unit, and South Central Timor Police who prefer persuasive methods; (2) inadequate infrastructure, where only 12 of the 44 landfills are operational; (3) low levels of legal awareness among the community; (4) cultural habits such as the practice of burning waste; (5) lack of coordination between institutions; and (6) instability in the application of administrative sanctions as an initial step before criminal sanctions. This study also discusses the types of administrative sanctions (such as warnings, fines, and permit revocation) and criminal sanctions (six months imprisonment or a fine of IDR 50 million) contained in the regulation, as well as the differences between existing provisions and practices in the field. The findings of this study demonstrate the importance of combining strong law enforcement, capacity building of officers, infrastructure improvements, and local culture-based educational approaches to address the waste problem comprehensively.